Analisis Konten Film Dirty Vote di Tiktok dalam Mempengaruhi Persepsi Masyarakat - Tamara Nur Fauziyah; Diryo Suparto; Didi Permadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze how the content of the Dirty Vote film circulating on TikTok Social Media influences public perception of the election process and the results of the 2024 Election. The film